Analisis Stabilitas Tanggul Sungai Citonjong Kabupaten Pangandaran - Ilham, Ilham (Jurnal Komposit: Jurnal Ilmu-ilmu Teknik Sipil, 2025)
The Citonjong River, located within the Ciwulan-Cilaki Watershed (DAS) in West Java, frequently experiences flooding due to reduced catchment capacity, sedimentation, and embankment instability. This study analyzes the stability of the Citonjong River embankment at four design segments (TPT 2.5 m, 3.6 m, 4.5 m, and 5.0 m) using GEO5 2022 software. The analysis includes the stability of cantilever structures, pile capacity, slope stability, and lateral deformation under both static and seismic conditions, with low water levels and flooding. Geotechnical parameters were obtained from field investigations, while structural parameters adhere to the SNI 8460-2017 standards. The results indicate that all segments meet the minimum safety factors for overturning (1.5 static, 1.1 seismic), slope stability (1.5 static, 1.1 seismic), and vertical bearing capacity (2.5), with lateral deformation remaining below the 60 mm threshold. Recommendations include the installation of erosion protection, such as gabions or riprap, at river bends to enhance the passive resistance of the Continuous Concrete Sheet Piles (CCSP).